Hand Hygiene Compliance Rates in 9 Pediatric Intensive Care Units Across Europe: Results from the Reducing Antimicrobial use and Nosocomial Infections in Kids Network. Issue 10 (29th July 2022) - Kopsidas, Ioannis; De Luca, Maia; Bielicki, Julia; Blázquez-Gamero, Daniel; von Both, Ulrich; Ciliento, Gaetano; Epalza, Cristina; Goycochea Validivia, Walter Alfredo; Kolberg, Laura; Lutsar, Irja; Machaira, Maria; Neth, Olaf; et al.
Abstract : A unified surveillance mechanism for hand hygiene and hospital-acquired infections for pediatric wards is lacking in Europe. We managed to setup such a mechanism in 9 pediatric intensive care units in 7 European countries, using World Health Organization's definitions and common methodology which allows for benchmarking among units and countries. Median hand hygiene compliance was found high 82.3% (interquartile range 71.6–94.5%), but gaps in practices were identified.